# How do you solve for x `(b^2•h^5•x)/(e^4•r)=(t^3k)/(y) `

### 2 Answers | Add Yours

`(b^2*h^5*x)/(e^4*r)=(t^3*k)/y`

By cross multiplying we get:

`b^2h^5xy=t^3ke^4r`

Since we have to solve for x, isolate 'x' on the left hand side and divide the right hand side by the rest portion of the left hand side(`b^2h^5y` ).

Therefore,` x=` `(t^3ke^4r)/(b^2h^5y)`

By rearranging, `x=(e^4t^3kr)/(h^5b^2y)` `=>` **answer**

`(b^2*h^5*x)/(e^4*r)=(t^3*k)/y`

First of all you want to get everything from the left side to the right except the "x". So, if you multiply both sides by `e^4*r` then it will cancel from the left side:

`(e^4*r)*(b^2*h^5*x)/(e^4*r)=(t^3*k)/y*(e^4*r)`

`b^2*h^5*x=(e^4*t^3*k*r)/y`

Then to get the x by itself on the left side of the equation, divide both sides by `b^2*h^5`

`(1/(b^2*h^5))*(b^2*h^5*x)=((e^4*t^3*k*r)/y)*(1/(b^2*h^5))`

**Therefore,** `x=(e^4*t^3*k*r)/(h^5*b^2*y)`